Management of Stage I–II Testicular Germ Cell Tumours: Current Treatment Paradigm and Future Perspectives (Canadian Oncology Today, 2025)
Testicular cancer is the most common solid tumour in males aged 15–44 years, with an estimated 1,300 new cases in Canada in 2024. Over 90% are germ cell tumours (GCTs) originating from spermatocyte precursors, with most arising in the testes. Risk factors include cryptorchidism, gonadal dysgenesis, genetic syndromes such as Klinefelter syndrome, family history, and possibly cannabis use.This review summarizes the evidence‑based diagnosis and management strategies of clinical stage I (CSI) and II (CSII) testicular GCTs used at the Princess Margaret Cancer Centre (PM), highlighting potential clinical pitfalls and future directions.